Removal of Chemical Oxygen Demand (COD) from Synthetic Rubber Wastewater Via Foam Fractionation (FF) Method - A.Zainuddin, N.; M.Hafiz, W.; Harliza Abd Razak, Noor; Rohana Mohd Yatim, Siti (International Journal of Engineering and Technology, 2018)
Foam fractionation (FF) with Physical Chemical Process (PCP) is one of the methods introduced to treat wastewater from synthetic rubber which contains high Chemical Oxygen Demand (COD) concentration. Wastewater sample from two different synthetic rubber industry which are Company A (A) and Company B (B) were used in this research. Batch reactor column FF of 40 cm height with an internal diameter of 8 cm was designed. The compressor air introduced into the reactor thru diffuser to produce bubbles at a constant pressure of 0.2 bar. The effect of aeration time (10,20,30,40 and 50 minutes) were investigated on the COD removal. Comparison on percentage (%) of COD removal by FF followed by PCP and PCP only were investigated. For PCP, chemical used was Polyaluminium Chloride (PAC) 18%, Sodium Hydroxide (NaOH) 48% and anionic polymer. COD value for raw sample and treated sample was tested using COD reagent in vial, reactor and spectrometer. The best aeration time for A is 10 minutes and B is 40 minutes. COD removal for A is 46%, from 32250 mg/l to 17550 mg/l and B is 23% from 1260 mg/l to 979 mg/l. FF is more efficient for removal of COD in high concentration of the wastewater. However, difference between FF combine with PCP versus PCP only for A is 1% and for B was unsuccessful. Therefore, FF technique is not effective method for COD removal.Â Â